Analysis of Volatile Organic Compounds in Virgin Coconut Oil and their Sensory Attibutes - Dayrit, Fabian M (Archīum Ateneo, 2011)
The volatile compounds in the headspace of twenty-four commercial virgin coconut oil (VCO) samples prepared by different methods (i.e. expeller, centrifugation, and fermentation with and without heat) were analyzed by solid phase microextraction-gas chromatography mass spectrometry (SPME-GCMS). The following volatile organic compounds (VOCs) were identified: ethyl acetate, acetic acid, 2-pentanone, hexanal, n-octane, 2-heptanone, limonene, nonanal, octanoic acid, ethyl octanoate, δ-octalactone, ethyl decanoate, δ-decalactone, and dodecanoic acid. Fermentation-produced samples were found to have higher levels of acetic acid and free fatty acids in the headspace compared to VCO produced using the centrifuge and expeller methods. Descriptive sensory analysis of the VCO samples by a trained panel was carried out to determine its sensory attributes and to correlate the volatile compounds that are responsible for VCO aroma. Principal components regression (PCR) of the SPME-derived analytical and sensory data indicates that lactones impart coconut-like aroma, while octanoic acid is mainly responsible for the rancid and acid aroma. SPME-GCMS can be used to differentiate VCO produced by physical means from fermentationproduced samples and can be used as a method to monitor VCO product quality.